Teori Kedatangan Islam Hingga Proses Islamisasi di Nusantara: Theory of the Arrival of Islam to the Process of Islamization in the Archipelago - Faridi, Faridi; Nur Hakim (LPPM Institut Studi Islam Sunan Doe, 2022)
This research focuses on knowing the theory of the coming of Islam to the process of Islamization in the archipelago. The method used in this study is through a literature review. Researchers collected secondary data regarding the theory of the arrival of Islam to the process of Islamization in the archipelago. Meanwhile, the data analysis technique uses the data triangulation method. The result of this research is that the process of Islamization in Indonesia is difficult and long, and is based on various ideologies. The indigenous people embraced Islam progressively incorporating Islam into the customs, conventions, and arrangements of the daily life of the local population. As suggested by the theorists above, this mentality has contributed to creating Muslim communities in coastal locations that were originally centers of contact between local residents and other nationalities, especially from Arabs, Persians, Indians, Bengalis, Chinese, and Turks. The presence of other nations is indicated by the existence of settlements in Indonesia such as Pakojan (Arabic village), Pachinan (Chinese village), Keling (Indian village), and so on. Indigenous groups who had become Muslim were politically formalized in the form of Islamic kingdoms in the area from the start.